Single-Ended Fast Protection for Transient Power of Multi-Terminal Flexible and Direct Power Grids Containing Renewable Energy - Shan, Jieshan; Tian, Xincui; Dai, Yue; Shu, Hongchun; Chang, Yong; Song, Jian (Frontiers in Energy Research, 2021)
With the proposal of carbon peak goal, the multi-terminal flexible DC grid containing various renewable energy becomes the one of main ways of renewable energy power transmission. Thus, it is increasingly important to improve its transmission reliability and stability. This paper proposes a single-ended protection principle based on the analysis method of transient power change for the "mesh structure" ring-shaped flexible direct current (DC) grid. Based on the propagation characteristics of voltage, current, and anti-traveling waves during fault period, the transient power variation coefficient based on SOD transformation is introduced to distinguish the internal and external faults. Besides, simulation based on PSCAD/EMTDC platform under Zhangbei four-port network verifies the effectiveness of proposed protection principle under various fault conditions. Meanwhile, the protection criterion is designed according to the difference in the change coefficient of the transient power SOD within and outside the fault time zone. Moreover, the setting value of protection start is obtained by analyzing the simulation results, thus a set of fast and reliable single-ended fast protection for the same-side short-time window transient power enhanced flexible straight power grid is developed via the combination with starting criterion of voltage sudden change.